القيد في السجل التجاري الالكتروني - علاق, مروة (جامعة الوادي.University eloued, 2022)
نستخلص في الأخير على أن التكنولوجيا أصبحت أمر ضروري في عصرنا الحالي لذلك نجد معظم دول العالم انتهجت مشروع رقمنة السجل التجاري الإلكتروني الذي أصبح مفروضا و يتماشى مع التطورات الاقتصادية لسنة 2022 الحاصل في دول العالم فأصبح هذا الموضوع في طور الإنجاز و الذي بدوره يقضي على مشاكل عديدة أهمها مشاكل التزوير في المحررات الإلكترونية و القضاء مشاكل التزوير الإدارة و التجار والمتعاملين فيما بينهم ، لتسجيل في السجل التجاري الإلكتروني إلتزام يقع على عاتق التاجر سواء كان التاجر طبيعي أو معنوي فهو عبارة عن سجل و دفتر تمسكه جهة رسمية إدارية أو قضائية يدون فيها كل معلومات و البيانات المتعلقة بالأشخاص ونشاطاهم تجاري من أجل دعم الثقة و الإطمئنان فيما بين التجار و المتعاملين الاقتصاديين معهم ، فهو عبارة عن أداة إشهارية و إعلامية واسعة لتاجر، كما يوضح لنا جميع مشروعات التجارية و النشاطات الاقتصادية و الأعمال التجارية في البلاد كما يلزم أن يكون القيد داخل البلاد كما يلزم أن يقدم المعلومات الصحيحة التي وضعها المشرع الجزائري ، فعدم تقديم معلومات متعلقة بصاحب السجل تؤدي إلى عقوبة مدنية و جزائية و غرمات مالية لهذا نجد أن المشرع الجزائري ألزم بحماية السجل التجاري فلدينا نوعان من سجل تجاري محلي موجود في كل ولاية وسجل مركزي يوجد مقره في الجزائر . Finally, we conclude that technology has become a necessity in our time, so we find that most countries of the world have adopted the project of digitizing the electronic commercial registry, which has become imposed and is in line with the economic developments of 2022 taking place in the countries of the world, so this topic is in the process of being completed, which in turn eliminates many problems The most important of these are the problems of forgery in electronic documents and the judiciary. Problems of forgery. Management, merchants, and those dealing with each other. To register in the electronic commercial registry is an obligation that falls on the merchant, whether the merchant is natural or legal. It is a record and book maintained by an official, administrative or judicial body in which all information and Data related to people and their commercial activities in order to support trust and confidence among merchants and economic dealings with them. He must also provide the correct information set by the Algerian legislator, as failure to provide information related to the holder of the record leads to civil and criminal penalties and financial fines. That is why we find that the Algerian legislator is obligated to protect the commercial register. We have two types of local commercial register located in each state and a central register located in Algeria.
م.س.ع .22
Keywords: القيد- السجل التجاري - الالكتروني; Registration - commercial register - electronic